ANALISIS OPERATIONAL EFFICIENCY DAN COST EFFICIENCY RATIO TERHADAP NET PROFIT MARGIN - Muliyadi Jaya (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
This research aims to examine the influence of operational efficiency ratio (OER) and cost efficiency ratio (CER) toward net profit margin (NPM) at Bank Rakyat Indonesia The background of this research done is due to the bank’s low rate in obtaining NPM.Based on the classical assumption test’s result, the two independent variables chosen in this research are normally distributed with no disorder found. According to the correlation test’s result, it is found that OER correlates to the NPM as high as 95.6 % while the CER correlates to the NPM as high as 92.7 %. In addition, based on the R-square test’s result, it is found that both independent variables are responsible as high as 91.6% for each change in the NPM.Based on the F test, it is found that both independent variables, including OER & CER have significant influence toward NPM simultaneously, in which the P-value less than 0.05 (5%).The T test’s result, however, shows that OER has negative and effect toward NPM partially, while the CER has the positive effect and the two variables have no significant effect partially. Therefore, the stepwise test is required to be done in order to get which variable that is significant partially. And this results that OER has significant and negative effect toward NPM partially with P-value less than 0.05 (5%) and t-calculated value [-8.030] > t-table [1.860]